2012
DOI: 10.1111/j.1440-1746.2011.06921.x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of gastroesophageal reflux disease in Korea and associated health‐care utilization: A national population‐based study

Abstract: The prevalence of GERD increased rapidly from 2005 to 2008. The rapid increase of PPI use reflects the real increase in the prevalence of GERD and demand for health care. Middle-aged people and women had a high frequency of GERD visits. Therefore, GERD might be a significant disease burden in Korea.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
54
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(57 citation statements)
references
References 15 publications
(33 reference statements)
2
54
1
Order By: Relevance
“…and its prevalence in the Korean general population is 2~20% [33]. Prevalence of appetite loss and GERD have not been systematically compared in other reports, but the frequencies of GERD in our three parkinsonian groups were slightly higher than that in the Korean general population (7.3%) [34].…”
Section: Discussionmentioning
confidence: 93%
“…and its prevalence in the Korean general population is 2~20% [33]. Prevalence of appetite loss and GERD have not been systematically compared in other reports, but the frequencies of GERD in our three parkinsonian groups were slightly higher than that in the Korean general population (7.3%) [34].…”
Section: Discussionmentioning
confidence: 93%
“…A nationwide study on reflux oesophagitis in China yielded a prevalence of 17.8% 16. Kim et al 17 reviewed National Health Insurance statistics for Korea and showed an increase in the diagnosis of GORD from 4.59% in 2005 to 7.27% in 2009.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, according to a nationwide survey, the incidence of GERD in Korea was 7.27% in 2008 and is continuously increasing 2. After introduction of proton pump inhibitors (PPIs), medical therapy became the first-line therapy for chronic GERD and has high efficacy.…”
Section: Introductionmentioning
confidence: 99%